MODERASI BERAGAMA PADA MASA WALISONGO NUSANTARA - Uswatun Khasanah, Siti; Muhayar, Marhadi; Nur Ramadhan, Nadiah (Institut PTIQ Jakarta, 2023)
The aim of this research are 1. to examine and analyze the Walisongo concept of religious moderation in terms of the nine keywords for religious moderation of the Ministry of Religion of the Republic of Indonesia, which include: a. humanity, b. public benefit, c. fair, d. balanced, e. obey the constitution, f. national commitment, g. tolerance, h. non-violence and. i. respect for tradition. 2. To analyze the relevance of the Walisongo concept of religious moderation to current religious moderation practices. This research uses qualitative methods and includes types of literature research. The data collection technique uses a documentary method by tracing primary and secondary data sources. The results of this research show that the concept of Walisongo moderation is seen from the nine key words for religious moderation of the Indonesian Ministry of Religion, namely (1) Humanity; Walisongo's preaching teachings emphasize empathy and a hard work ethic in the form of generosity, poverty alleviation, efforts to create prosperity, social solidarity and mutual cooperation (2) Public Benefit; Walisongo spreads Islam with morals, knowledge and principles of peace (wasathiyah) to bring solutions to society. (3) Fair; As a ruler, Walisongo not only protects Muslims, but also non-Muslims, such as Raden Paku's preaching which bestowed the title of Prabu Satmata as a symbol of the power of the Siwais (Shiwais) as well as a form of spiritual egalitarianism representing the majority of people who follow the Hindu Shiva teachings ( 4) Balanced; Walisongo believes that religion is part of obedience to Allah (hablum minallah) and maintaining social relations (hablum minannas). (5) Obey the Constitution; The da'wah material applied by Walisongo is material related to faith, sharia and muamalah. By adopting methods and methods developed by Sunni Sufi figures and based on QS An-Nahl verse 125. (6) National Commitment, including the oath of allegiance to Majapahit, the establishment of the Kutara Manawa Dharmashastra law as the Demak constitution, the transformation of Majapahit nationalist values with Islamic values. (7) Tolerance; includes a balance between the Hindu cosmology of Nawa Dewata and the Sufi cosmology of Walisongo, giving the title of Prabu Satmata and adopting the Majapahit model of power, respect for the values of other religious beliefs and beliefs. (8) Non-violence includes expanding the influence of Islam through kinship relations with community leaders and nobles, diplomacy with Majapahit leaders, and preaching based on sovereignty, religious humanism (9) Accommodation of local culture includes the Islamization of Hindu-Buddhist and Kapitayan terms, modification of wayang story norms with Islamic values, alignment of Islamic values with Hindu-Buddhist, Kapitayan and Tantra Bhairawa religious traditions.